Alterations of Platelet Aggregation Kinetics with Ultraviolet Laser Emission: The “Stunned Platelet” Phenomenon - Topaz, On; Minisi, Anthony J.; Bernardo, Nelson L.; McPherson, Richard A.; Martin, Erika; Carr, Sheryl L.; Carr, Marcus E., Jr. (Thrombosis and Haemostasis, 2001)
Platelets, a major constituent of thrombus, play a crucial role in the pathogenesis of acute ischemic coronary syndromes. The effect of ultraviolet laser emission on platelets within thrombi is unknown. The effects of increasing levels of laser energy on platelets in whole blood were investigated. Blood samples were obtained by aseptic venipuncture and anticoagulated with 3.8% sodium citrate. Samples were exposed to increased levels (0, 30, 45, 60 mJ/mm2; 25 Hz) of ultraviolet excimer laser fluence (308 nm wave-length) and then tested for ADP and collagen induced platelet aggregation, platelet concentration, and for platelet contractile force (PCF) development. Scanning electron microscopy was used to detect laser induced morphologic changes of platelets and by flow cytometric analysis to detect changes in expression of platelet surface antigens p-selectin (CD 62) and glycoprotein IIb/IIIa (CD 43). Exposure to excimer laser energy produced dose dependent suppression of platelet aggregation and force development (“stunned platelets”). ADP aggregation decreased from 8.0 ± 1.1 Ohms (mean ± SEM) to 3.7 ± 0.8 Ohms (p 0.001) to 2.7 ± 0.6 Ohms (p 0.001) and to 1.8 ± 0.5 Ohms (p 0.001) as the laser energy increased from 0 to 30 to 45 to 60 mJ/mm2, respectively. Collagen induced aggregation decreased from 21.4 ± 1.4 Ohms to 15.7 ± 1.2 Ohms (p 0.001) to 11.7 ± 1.1 Ohms (p 0.001) and to 9.9 ± 1.0 Ohms (p 0.001), in response to the same incremental range of laser energy. Platelet contractile forces declined from 34,500 ± 3700 to 27,800 ± 2700 dynes as laser energy increased from 0 to 60 mJ/mm2 (p 0.03). Platelet concentration did not change with increasing laser energy. The expression of platelet surface antigen p-selectin (CD 62) remained stable through increasing levels of laser energy exposures while the percentage of CD 43 positive platelets significantly increased with exposure to laser energy, yet the level of expression did not exceed 0.5% of cells. Thus, aggregation kinetics are altered in platelets exposed to ultraviolet laser energy as manifested by decreased platelet aggregation and reduction in platelet force development capability. The response is dose dependent and most pronounced at higher energy levels such as 60 mJ/mm2.
Keywords: Platelets; thrombus; laser; coronary; aggregation